Pengaruh Kesadaran dan Pemahaman Wajib Pajak Terhadap Pembayaran Pajak Kendaraan Bermotor di Kecamatan Astanaanyar Kota Bandung - Triana Novianti; Kasan K. Suantha (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of taxpayer awareness and understanding on motor vehicle tax payments in Astanaanyar District, Bandung City. The research method used is a survey with a quantitative approach. Data were collected through questionnaires distributed to 100 randomly selected motor vehicle taxpayers in the Astanaanyar District area. Data analysis was carried out using multiple linear regression to test the simultaneous and partial effects between the independent variables (taxpayer awareness and understanding) on ​​the dependent variable (motor vehicle tax payments). The results of the study showed that both taxpayer awareness (β = 0.238, ρ = 0.003) and understanding (β = 0.196, ρ = 0.001) have a positive and significant effect on motor vehicle tax payments. Furthermore, the results of the determination test (Adjusted R Square = 0.360) showed that around 36.0% of the variation in motor vehicle tax payments can be explained by taxpayer awareness and understanding. This study implies the importance of efforts to increase taxpayer awareness and understanding through effective socialization and education to increase the level of compliance in paying motor vehicle taxes in Astanaanyar District.